Study of press translation difficulties - Fattah, Ammar Ibrahim (Al-Adab Journal, 2020)
The present work consists of studying and analyzing the difficulties of journalistic translation from Spanish to Arabic, which is one of the types of translation that are very important, shedding light on the fundamental criteria that lead to the correct translation by the translator.